GIS as new tools and approach in state planning and monitoring: the experience of Negeri Sembilan, Malaysia - Yaakup, Ahris (2006)
Malaysian planning methodology has changed over the years as emphasis has shifted from producing plan, which described a state of affairs expected of some future date, to one which acknowledged the continuous and cyclical nature of planning. Thus planning should be based on the identification of needs and goals, the formulation and evaluation of alternative courses of action and monitoring of adopted programmes. Using examples from current Geographical Information Systems (GIS) implementation projects, this paper will discuss GIS development and application for planning and monitoring of development in one of the Malaysian states, Negeri Sembilan. The development include a well-integrated and comprehensive database which is part of the important elements that could determine the ultimate success of GIS application in plan making. A distinctive feature of the Negeri Sembilan GIS (GIS9) that was developed for this purpose is that it is capable of operating on two distinct levels of planning – the state and district level. It is used to assist decision-making, taking into account among other things, the current scenarios of the proposed development, physical constraint and future impacts. The monitoring system that has been developed for both the state and district levels make it possible to evaluate the success of plan implementation. While the adopted data sharing framework is seen as a strong basis for extension of GIS development as well as integration and coordination in all state and local agencies involved in ensuring the success of the implementation of state development plan. The implementation of GIS9 has also contributed to raising recognition of the importance of vertical integration of the developed and maintained datasets at regional and local levels. This paper will discuss the approach and overall strategies employed in the preparation of GIS9 database and development plans monitoring system for the Negeri Sembilan State.